2019
DOI: 10.1371/journal.pone.0214223
|View full text |Cite
|
Sign up to set email alerts
|

Passive heating and glycaemic control in non-diabetic and diabetic individuals: A systematic review and meta-analysis

Abstract: ObjectivePassive heating (PH) has begun to gain research attention as an alternative therapy for cardio-metabolic diseases. Whether PH improves glycaemic control in diabetic and non-diabetic individuals is unknown. This study aims to review and conduct a meta-analysis of published literature relating to PH and glycaemic control.MethodsElectronic data sources, PubMed, Embase and Web of Science from inception to July 2018 were searched for randomised controlled trials (RCT) studying the effect of PH on glycaemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…There is also evidence of the potentially deleterious effect of chronic heat exposure on carbohydrate metabolism, even in healthy subjects, one example being the recent study showing that carbohydrate metabolism was disrupted in this condition [29]. Since common glycoregulatory hormones and biomarkers do not explain the exaggerated increase in blood glucose in warm environmental temperature, it has been suggested that insulin resistance could develop in this condition [30].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of the potentially deleterious effect of chronic heat exposure on carbohydrate metabolism, even in healthy subjects, one example being the recent study showing that carbohydrate metabolism was disrupted in this condition [29]. Since common glycoregulatory hormones and biomarkers do not explain the exaggerated increase in blood glucose in warm environmental temperature, it has been suggested that insulin resistance could develop in this condition [30].…”
Section: Discussionmentioning
confidence: 99%
“…Heat therapy has recently been targeted as a potential vehicle to evoke these positive thermal-induced adaptations in those precluded from undertaking exercise. Experimental investigations, large cohort surveys and reviews have expressed the potential for passive heating to improve physical and mental health in patients with cardiovascular disease (Brunt et al, 2016a,b;Maeda et al, 2018), diabetes (Kimball et al, 2018;Maley et al, 2019), peripheral arterial disease (Akerman et al, 2019), and depression (Janssen et al, 2016).…”
Section: Responses To Active (Exercise Heat Acclimation) and Passive mentioning
confidence: 99%
“…Recent research has shown positive therapeutic effects of passive heating for people with peripheral arterial disease (Neff et al, 2016;Akerman et al, 2019), chronic heart failure (Kihara et al, 2002;Ohori et al, 2012), diabetes (Hooper, 1999), and depression (Janssen et al, 2016). Passive heating also improves a range of health markers, including cardiovascular health indices, such as vascular function, blood pressure, and arterial stiffness (Brunt et al, 2016a,b), as well as metabolic health and glycemic control (Janssen et al, 2016;Kimball et al, 2018;Ely et al, 2019;Maley et al, 2019). Several mechanistic pathways may underpin these adaptations, including improved cellular respiration , circulating factors (Brunt et al, 2019), and vascular shear stress (Tinken et al, 2009;Thomas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Passively elevating body temperature, by means of sauna bathing or hot water immersion (HWI) for example, is increasingly recognised as a strategy to promote cardiometabolic health (Hoekstra et al, 2020). The acute effects of whole-body passive heating methods are well-characterised, with recent research interest focusing on metabolic, inflammatory and vascular markers (Maley et al, 2019;Cullen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%